The Association of Research Collaboration and Bibliometrics Data with Citation Impact among Articlesbased on Scopus Q1 from Nursing Institutions in Thailand - ศรีสวัสดิ์ สุทธิศักดิ์ (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
This cross sectional study proposed to study characteristics ofresearch collaborationand bibliometrics datain international research articles of faculty of nursing, Mahidol university and other faculty of nursing in Thailand. Furthermore, this article indicatedassociation of research collaboration and bibliography on citation impact by using non-parametric of one-way ANOVA test (Kruskal-Wallis Test) for comparison citationin each collaboration groups. The log-linear regression model was used in next step to be consistent with the distribution of citation impact value was not normal distribution and right skewed. The sample size were 194 research articles of Thai faculty of nursing published in the Scopus database and journal in quartile ranking 1 for control same quality ofjournal publication. The Results shown that research articles had average number of authors about 4 (mean = 4.45; S.D. = 3.19) and average number of institutions about 2-3 (mean = 2.70; S.D. = 2.41). More than 63 percent of research articles were article with bilateral international collaboration and about 8.8 percent were article with multilateralcollaboration. The Result of Kruskal-Wallis Test revealed that articles with more than 6 authors has statistically significant higher citation rate than other groups. In term of log-linear regression analysis, factors that influenced citation rate per year such as number of references, number of authors and H-Index of first authors with R2 = 0.165 (Adjusted R2 = 0.138). For another independent variables (FWC Index), number of references was only one factor that can be significant influence factor. The result can be used to planning for international research publication to increase the quality of research and increase opportunities for research to be utilized. Researcher must consider literature review to cover the research field and the importance thing to consider is about research collaboration with famous researcher or researcher with high impact in the field.